Analysis of year four pupils' difficulties in solving mathematical problems involving fraction - Mohd Mokhtar, Mohd Azarul; Mohd Ayub, Ahmad Fauzi; Said, Rozita @ Radhiah; Mustakim, Siti Salina (Human Resource Management Academic Research Society, 2019)
Problem-solving is a very important element of Mathematics learning. Unfortunately, the results of the Trends in International Mathematics and Science Study (TIMSS) shows that most pupils are still weak in math problem solving skills. Furthermore, fraction is also a difficult topic for pupils to master. Therefore, this research aims to analyse the types of difficulties faced by Year Four pupils in solving mathematical problems in the fraction topic. The sample was divided into two groups, primary school pupils and math teachers. Data collection was conducted through structured interviews, document analysis and survey testing. Data analysis was conducted using descriptive statistics and content analysis. The results show that there are some difficulties in solving problems in fraction, which are: 1) Pupils have difficulty in understanding the keywords and fail to convert to the correct mathematical sentence, 2) Pupils are weak in mathematics comprehension, 3) Pupils are weak in basic concepts and 4) Pupils do not like to read long-term math questions. Therefore, the findings of this study will encourage teachers to come up with more effective teaching strategies to help pupils to answer mathematical questions better.